2015
DOI: 10.5539/gjhs.v8n2p27
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence During Pregnancy and Women's Health-Related Quality of Life

Abstract: Domestic violence during pregnancy is a major health problem with significant psychological and physical impairments for pregnant women. To assess the relationship between domestic violence during pregnancy and women’s health-related quality of life (HRQoL), a cross-sectional study was conducted on 341 postnatal women who referred to urban health care centers in Gachsaran, Islamic Republic of Iran. Domestic violence was assessed using a questionnaire modified from the Abuse Assessment Screen (AAS), and Iranian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
18
1
2
Order By: Relevance
“…Thirteen studies were conducted during the first trimester of pregnancy [ 17 , 20 , 22 , 23 , 26 , 30 , 38 40 , 44 47 ], eleven were from the second trimester [ 14 , 16 , 24 , 35 , 38 – 41 , 45 , 46 , 48 ], eighteen were from the 3rd trimester [ 14 , 18 , 19 , 27 , 29 , 31 , 33 , 34 , 37 – 42 , 46 , 48 50 ] and six studies focused on the entire pregnancy [ 25 , 28 , 32 , 36 , 43 , 51 ]. In measuring the quality of life, nineteen studies used SF-36 [ 14 , 17 19 , 21 , 22 , 25 27 , 30 , 33 , 34 , 38 – 41 , 44 , 46 , 51 ], twelve studies used SF-12 [ 16 , 20 , 23 , 24 , 28 , 29 , 35 , 42 , 43 , 46 , 48 , 50 ], two studies used the WHOQOL Brief [ 32 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies were conducted during the first trimester of pregnancy [ 17 , 20 , 22 , 23 , 26 , 30 , 38 40 , 44 47 ], eleven were from the second trimester [ 14 , 16 , 24 , 35 , 38 – 41 , 45 , 46 , 48 ], eighteen were from the 3rd trimester [ 14 , 18 , 19 , 27 , 29 , 31 , 33 , 34 , 37 – 42 , 46 , 48 50 ] and six studies focused on the entire pregnancy [ 25 , 28 , 32 , 36 , 43 , 51 ]. In measuring the quality of life, nineteen studies used SF-36 [ 14 , 17 19 , 21 , 22 , 25 27 , 30 , 33 , 34 , 38 – 41 , 44 , 46 , 51 ], twelve studies used SF-12 [ 16 , 20 , 23 , 24 , 28 , 29 , 35 , 42 , 43 , 46 , 48 , 50 ], two studies used the WHOQOL Brief [ 32 ...…”
Section: Resultsmentioning
confidence: 99%
“…et al (2012) Italy [ 40 ] a,b Case-controlled study 115 87,79 Medical Outcomes Study Short Form 36 (SF-36) 19 Elsenbruch S. et al (2006) Germany [ 19 ] a,b Cross-sectional study 978 91,60% Medical Outcomes Study, Short Form 12 (SF-12) 19 Emmanuel EN et al (2012) Australia [ 50 ] a, b Longitudinal cohort study 630 77% Medical Outcomes Study Short Form 12 (SF-12) Version 2 17 Emmanuel EN et Sun J. (2014) Australia [ 42 ] a,b Longitudinal cohort study 605 60% Medical Outcomes Study, Short Form 12 (SF-12) 18 Fatemeh A et al (2010) Iran [ 32 ] a,b Cross-sectional study 600 Medical Outcomes Study Short Form 36 (SF-36) 12 Gezginç K et al, (2008) Turkey [ 35 ] b Cross-sectional study 55 WHO-QOL-BREF Questionnaire 14 Gharacheh M. et al, (2015) Iran [ 20 ] b Cross-sectional study 328 96% Medical Outcomes Study Short Form 36 (SF-36) 19 Haas JS et al (2004) USA [ 42 ] a, b Longitudinal cohort study 2854 63% Medical Outcome Study Short Form-36 (SF-36) 20 Hama K et al (2008) Japan [ 51 ] b Longitudinal cohort study 190 83% Medical Outcomes Study Short Form 36 (SF-36) version 2 14 Jomeen J., Martin CR; (2005) United Kingdom [ 21 ] a,b Cross-sectional stud...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies revealed that IPV during pregnancy was significantly associated with termination of pregnancy (24), premature rupture of membranes and increased risk of low birth weight (19), perinatal and neonatal mortality (25), and pre-term labour which increases in the number of caesarean section cases and hospitalization during pregnancy (26). Similarly, other studies showed that IPV during pregnancy is associated with increased risk of common mental disorders, postnatal depression, and poor health-related quality of life (27)(28)(29).…”
Section: What This Paper Addsmentioning
confidence: 98%
“…As investigações que se propõem a identificar os fatores determinantes de boa ou má QVRS são cada vez mais necessárias e imprescindíveis, pois podem subsidiar a elaboração e a implementação de políticas públicas que visem à melhoria da saúde física e mental das pessoas. Nesse sentido, é válido mencionar que diversos pesquisadores nacionais e internacionais detectaram que indivíduos expostos à violência apresentaram piores escores de QVRS em relação aos não expostos [13][14][15] .…”
Section: Introductionunclassified